2000
DOI: 10.1016/s0016-5085(00)81258-5
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of persistent mumps virus infection in inflammatory bowel disease

Abstract: Background and aim-There is controversy regarding whether paramyxovirus infection is causally associated with inflammatory bowel disease (IBD). The latest cohort study claimed that atypical measles and mumps infections in childhood may be risk factors for later IBD. This study was conducted to clarify the validity of a causal link between persistent mumps virus infection and IBD. (Gut 2001;48:637-641)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
4
0
1
Order By: Relevance
“…Investigations into a causal link between persistent mumps virus infection and IBD using anti‐mumps IgG EIA and RT‐PCR analysis reported no evidence of an association between mumps virus and CD . Our meta‐analysis of four comparison dataset of two studies provide some suggestion that mumps virus may be associated with a protective effect from CD (RR 0.922, 95% CI 0.838 to 1.016), although this did not reach statistical significance (Figure ).…”
Section: Measles Mumps and Rubellamentioning
confidence: 64%
“…Investigations into a causal link between persistent mumps virus infection and IBD using anti‐mumps IgG EIA and RT‐PCR analysis reported no evidence of an association between mumps virus and CD . Our meta‐analysis of four comparison dataset of two studies provide some suggestion that mumps virus may be associated with a protective effect from CD (RR 0.922, 95% CI 0.838 to 1.016), although this did not reach statistical significance (Figure ).…”
Section: Measles Mumps and Rubellamentioning
confidence: 64%
“…Although some identified a higher IBD risk [91,92] , viral parts were not isolated from intestinal tissue [93] and the direct link with IBD could not be established. While it was suggested that the immunological response to the virus might be involved in the process of IBD presentation, as was observed with the measles virus, no concluding evidence was found [94] .…”
Section: Mumps (Parotiditis)mentioning
confidence: 99%
“…However, the differences between the mean antibody titers of the controls and the subjects were only one or two dilutions. Recent work using reverse transcription-PCR (RT-PCR) has demonstrated no evidence of mumps virus P or HN genes in patients with inflammatory bowel disease (168). There does not yet appear to be a clear link established between HPIV and inflammatory or connective tissue disease.…”
Section: Clinical Syndromesmentioning
confidence: 99%